Revealing the Therapeutic Potential of Nigella Sativa Extract in Aspergillus Niger-Induced Otitis Externa: Anti-Inflammatory and Antioxidant Properties - Haitamy, Mohammad Nurrizki; Kariosentono, Harijono; Prayitno, Adi; Setiamika, Made; Soetrisno, Soetrisno; Nurwati, Ida; Cilmiaty AR, Risya (Trends in Sciences, 2024)
Otitis externa (OE), a fungal infection of the external auditory canal, often involving Aspergillus niger, can lead to OE externa, posing severe health risks. Establishing an animal model of OE induced by Aspergillus niger, this study aimed to evaluate the therapeutic potential of Nigella sativa (NS) extract, specifically its effect on inflammation and antioxidant activity in this OE animal model. The detection of Aspergillus niger on the 3rd day post-induction confirmed its thriving presence within the ear canal. NS extract, containing thymoquinone, significantly reduced the expression of IL-1B and TNF-a proteins. Notably, NS extract at 5 and 10 % showed comparable effects, surpassing the efficacy of topical miconazole. Evaluation of MDA protein expression, indicative of oxidative damage, revealed a significant decrease with NS extract treatment, especially at 5 % dosage. NS extract exhibited a notable decrease in subunit p50 and p65 proteins expression, particularly at the 5 % concentration. In conclusion, NS extract displayed promising anti-inflammatory effects on Aspergillus niger-induced otitis externa by modulating various inflammatory markers and pathways. These findings highlight the potential therapeutic role of NS extract in addressing inflammation associated with OE. HIGHLIGHTS Confirmation of Aspergillus niger presence in the ear canal on the 3rd day post-induction, establishing the infection model. Nigella sativa extract (NS), containing thymoquinone, significantly reduced the expression of pro-inflammatory proteins IL-1B and TNF-a. NS extract at 5 and 10 % concentrations demonstrated comparable or superior efficacy to topical miconazole, a common antifungal medication. Evaluation of malondialdehyde (MDA) protein expression showed a significant decrease with NS extract treatment, particularly at the 5 % dosage, indicating reduced oxidative damage. Notable decrease in the expression of inflammatory pathway-associated proteins p50 and p65 with NS extract treatment, especially at the 5 % concentration. GRAPHICAL ABSTRACT